Estimating Prevalence of Illicit Drug Use in Yunnan, China, 2011–15 - Zhang, Guanbai; Jiang, Heng; Shen, Jiucheng; Wen, Pinyuan; Liu, Xuebing; Hao, Wei (Frontiers in Psychiatry, 2018)
Background and Aims: Yunnan has been one of the provinces most afflicted by illicit drug use in China. However, there have been few systematic studies on the prevalence of illicit drug use in the area. Method: Using data on illicit drug users registered in the police system, this study aims to estimate the population size of illicit drug users and the annual prevalence of drug use in Yunnan from 2011 to 2015 using Zelterman’s capture-recapture method. Results: In the 15-64 year-old population, the estimated prevalence rate of any illicit drug use was 0.81% (0.76%-0.86%) in 2011 and 0.94% (0.90% -0.98%) in 2014, representing a significant increase. The prevalence rate of heroin use decreased from 0.67% (0.63%- 0.73%) in 2011 to 0.57% (0.53%-0.61%) in 2015, while the prevalence rate of methamphetamine use doubled from 0.20% (0.17%-0.24%) in 2011 to 0.48% (0.46%-0.50%) in 2015. The mean age of the 141,702 identified illicit drug users in Yunnan from 2011-15 was 32.2 years, and the majority were male, low educated, and peasants; nearly half were single and ethnic minorities. The ratio of the number of identified illicit drug users to the number of hidden users increased from 1:12 in 2011 to 1:5 in 2015. Conclusion: The prevalence of illicit drug use in Yunnan has been increasing. Although the prevalence of heroin use decreased, methamphetamine use increased dramatically from 2011 to 2015. Preventive strategies that are more effective in reducing illicit drug use are urgently needed in Yunnan.